2008
DOI: 10.1111/j.1526-4610.2008.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Disability Awareness Campaign in Asia: Migraine Assessment for Prophylaxis

Abstract: Migraine is the most common headache diagnosis in neurological services in Asia. The prevalence of migraine was higher in countries with higher referral rates of patients to neurological services. Migraine remains underdiagnosed and under-treated in this region even though a high disability was found in patients with migraine. Probable migraine was adopted into the migraine diagnostic spectrum by neurologists in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 17 publications
4
31
1
Order By: Relevance
“…In a study performed in Turkey [1], a total of 66.4% of all patients reported headache in neurology outpatient clinics and 36.8% of patients with headache were diagnosed as migraine according to International Headache Society (IHS) criteria. Our finding suggested that the prevalence of migraine among neurological headache outpatients in China is somewhat lower than that in other Asian countries [6]. The discrepancy may attribute to the different study methodology, genetic and socio-cultural factors in different countries.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In a study performed in Turkey [1], a total of 66.4% of all patients reported headache in neurology outpatient clinics and 36.8% of patients with headache were diagnosed as migraine according to International Headache Society (IHS) criteria. Our finding suggested that the prevalence of migraine among neurological headache outpatients in China is somewhat lower than that in other Asian countries [6]. The discrepancy may attribute to the different study methodology, genetic and socio-cultural factors in different countries.…”
Section: Discussioncontrasting
confidence: 56%
“…Approximately 19.5% of all neurological outpatients complained of headache and the prevalence of migraine was 23.8% among headache patients. A multinational cross-sectional study conducted in 8 Asian countries indicated that migraineurs comprised the majority of patients who consulted their neurologists with headache complaints, the proportion ranging from 50.9% to 85.8% across different countries [6]. In a study performed in Turkey [1], a total of 66.4% of all patients reported headache in neurology outpatient clinics and 36.8% of patients with headache were diagnosed as migraine according to International Headache Society (IHS) criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a clinical study from a headache center in east Hungary [4], migraine was the most common headache, while TTH patients reported more severe disability than migraines. A study from Asia [5] also showed that migraine was the most common headache diagnosis in neurological services. A population survey in Chile [6] indicated that migraineurs were more likely to consult doctors than TTH patients.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Migraine was ranked as the seventh-highest specific cause of disability and the third most prevalent disorder worldwide in Global Burden of Disease Survey 2010, with a prevalence of 6.5% in men and 18.2% in women. [4][5][6] however, it still remains under-reported, under-diagnosed and under-treated. Highest prevalence is found in age groups 25 to 55 years.…”
Section: Introductionmentioning
confidence: 99%